Assessing public spending efficiency in 20 OECD countries - Afonso, António (2016)
This study follows the framework of Afonso, Schuknecht, and Tanzi (2005), aiming to look at the public expenditure of 20 OECD countries for the period 2009-2013, from the per- spective of efficiency and assess if these developed countries are performing efficiently compared to each other. Public Sector Performance (PSP) and Public Sector Efficiency (PSE) indicators were constructed and Data Envelopment Analysis was conducted. The results show that the only country that performed on the efficiency frontier is Switzerland. The average input-oriented efficiency score is equal to 0.732. That is, on average countries could have reduced the level of public expenditure by 26.8% and still achieved the same level of public performance. The average output-oriented efficiency score is 0.769 denoting that on average the sample countries could have increased their performance by 23.1% by employing the same level of public expenditure.